Manejo financiero de una empresa de servicios dedicada al alquiler de equipos para construcción ubicada en la ciudad de Duitama – Boyacá. (2020)
This process may be carried out with the study and analysis of the financial statements. According to Garcia (2014), finance can be defined as the grouping of mercantile activities that are related to the money generated by businesses, banks and financial institutions, both national and international. That is why in this case study, the objective is to know, through the analysis that is carried out on the financial statements, how the company is managing its income.Once the results of the analysis of the financial indicators are obtained, the most critical will be taken, this in order to propose the necessary improvements for the growth and development of the company.